2004
DOI: 10.2165/00002512-200421140-00003
|View full text |Cite
|
Sign up to set email alerts
|

Rivastigmine in Frontotemporal Dementia

Abstract: In this open-label study, rivastigmine-treated patients were less behaviourally impaired, and caregiver burden was reduced, at 12 months, compared with baseline. The use of cholinesterase inhibitors in FTD warrants further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(93 citation statements)
references
References 23 publications
0
88
0
5
Order By: Relevance
“…27,29,30,32 Four quality B studies noted behavioral improvement without significant results, 12,28,34,36 two studies did not observe any significant behavioral change, 26,36 one study described behavioral worsening 33 and one study did not assess this aspect. 31 On the other hand, there were conflicting results from the studies that focused on the efficacy of treatment for cognitive impairment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27,29,30,32 Four quality B studies noted behavioral improvement without significant results, 12,28,34,36 two studies did not observe any significant behavioral change, 26,36 one study described behavioral worsening 33 and one study did not assess this aspect. 31 On the other hand, there were conflicting results from the studies that focused on the efficacy of treatment for cognitive impairment.…”
Section: Resultsmentioning
confidence: 99%
“…Seven quality B studies did not reveal any significant changes. [26][27][28]30,32,34 However, the Bromocriptine study showed a significant improvement in the mean time of utterance as compared to the placebo, 31 and one Memantine study found a significant increase in the total score of ADAS-Cog. 35 36 Two B studies did not evaluate cognitive functions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of antidepressants such as trazadone seem to help stabilize the behavioral symptoms, but, unfortunately, without an impact on cognition (Lebert et al 2004). Similar benefi ts have been found with the cholinesterase inhibitor rivastigmine (Moretti et al 2004), and the MAO-B inhibitor selegiline (Moretti et al 2002).…”
Section: Treatmentmentioning
confidence: 86%
“…Other areas where cholinesterase inhibitors may have a future role include the treatment of frontotemporal dementia (Moretti et al, 2004b), Korsakoff's syndrome (Cochrane et al, 2005), Huntington's disease (Petrikis et al, 2004) and, if evidence improves and is consistent, mild cognitive impairment (Saykin et al, 2000).…”
Section: Other Possibilitiesmentioning
confidence: 99%